Deutsch Österreichisch Schweizer Arbeitskreis Epilepsie (DACH AK): Geschichte und Idee - Mamoli, Bruno; Stefan, Hermann (Zeitschrift für Epileptologie, 2019)
A working group was founded 25 years ago to stimulate exchange of epileptological knowledge and personal experience between German, Austrian and in the following year Swiss colleagues. The spectrum of participants ranges from young colleagues in training to experienced epileptologists from private practices, hospitals and scientific institutions.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Courses; German speaking clinical and scientific forum; History; Working group Epileptology